Evaluation of a passive sampler for the speciation of metals in urban runoff water - Knutsson, J.; Knutsson, P.; Rauch, S.; Pettersson, T.; Morrison, Gregory (2013)
Metals in urban runoff water need to be monitored in order to estimate fluxes and assess their impact on the aquatic environment. Passive sampling is a useful and reliable emerging tool for measuring time averaged concentrations of metals in water bodies. This paper describes the deployment of a passive sampler to measure Cu, Ni and Zn in an urban runoff water treatment facility. The concentrations derived from the passive samplers are compared to concentrations obtained from an automated water sampler which provides pooled spot water samples and to model predictions from the visualMINTEQ computer speciation code. Results show that visualMINTEQ predictions partly describe the metal speciation in non-equilibrium systems. In addition we conclude that passive samplers are useful for monitoring and characterization of metal speciation under chemodynamic conditions. © 2013 The Royal Society of Chemistry.